Threats of identity theft in cyberspace - case study - Wojciech Jakubiec (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2020)
We can certainly say that identity theft on the Internet is a growing criminal phenomenon. The perpetrators’ actions are most often motivated by financial gain. The article discusses selected issues concerning so-called Internet fraudsters. In particular, it draws attention to the actions taken in cyberspace and the risks that accompany such decisions. I point out that the most vulnerable to identity theft are elderly people who do not even know basic security procedures. The article not only draws attention to the dangers themselves but also describes the way criminals act. It also states that in order to minimize the risks faced by network users, attention should be paid to training needs related to with security in cyberspace. An important aspect of this is to draw attention to the risks associated with personal data improperly stored on electronic media integrated into the Internet.